Renal Cell Carcinoma Clinical Management - Campbell, Steven C.; Rini, Brian I.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana Press, 2013)
Renal Cell Carcinoma: Clinical Management provides a comprehensive, state-of-the art review of this field, and will serve as a valuable resource for clinicians, surgeons and researchers with an interest in kidney cancer. The volume reviews new data about risk factors for the disease, profiles the new staging system for renal cell carcinoma (RCC), highlights our current understanding of familial syndromes of RCC and their molecular genetics, and provides new perspectives about imaging of renal tumors. For localized disease, a greater appreciation of nephron-sparing approaches and the importance of preservation of renal function is discussed in detail. Advances in surgical techniques are highlighted. For metastatic disease, the molecular biology of kidney cancer is reviewed in a concise and understandable manner, including the data that has fostered novel targeted approaches that have revolutionized management. The several landmark phase III targeted therapy trials published in the last few years are placed in context with respect to current management.
Section I: Localized Disease -- 1.Etiology of RCC: Incidence, Demographics, and Environmental Factors -- 2.Pathology of Renal Cell Carcinoma -- 3.Familial Renal Cell Carinoma -- 4.Imaging of Renal Cell Carcinoma -- 5.Prognostic Factors for Localized Renal Cell Carcinoma -- Section II: Management of Localized RCC -- 6.Assessment of Oncologic Risk for Clinical Stage T1 Renal Tumors and the Emerging Role of Renal Mass Biopsy -- 7.Radical Nephrectomy for Localized Renal Tumors: Oncological and Renal Functional Considerations -- 8.Nephron-Sparing Surgery for Renal Cancer -- 9.Thermal Ablation -- 10.Active Surveillance of the Small Renal Mass -- Section III: Locally Advanced Disease -- 11.Locally Advanced Renal Cell Carcinoma -- 12.Neoadjuvant Targeted Therapy and Consolidative Surgery -- Section IV: Advanced Disease -- 13.Biology of RCC (VEGF, mTOR, immune aspects) -- 14.Prognostic Factors in Advanced Renal Cell Carcinoma -- 5.Integration of Surgery in Metastatic Renal Cancer -- 16.Immunotherapy for Renal Cell Carcinoma -- 17.Targeted Therapy: Vascular Endothelial Growth Factor (VEGF) -- 18.mTOR in Renal cell carcinoma -- 19.Palliative and Supportive Care for Renal Cancer.
Keywords: Medicine; Oncology; Urology; Medicine & Public Health; Urology/Andrology.; Oncology